Glycolysis and Heavy Menstrual Bleeding - Rytkönen Kalle T (SPRINGER HEIDELBERG, 2025)
Menstrual cycle is a major determinant in female reproductive health. In a recent report, Mao et al. (2022) associated deficient glycolysis with heavy menstrual bleeding. This commentary summarizes these recent findings and the importance of glycolysis and decidualization in endometrial function. It will also discuss if in the light of the recent findings menstrual bleeding is better conceived as a primary endometrial disorder inherent to endometrium or as a secondary endometrial disorder caused by other endometrial conditions.